The impact of motivational interventions for increasing physical activity - Aneci Sobral Rocha; Marcio Marega (Einstein (São Paulo), 2010)
ABSTRACT Objective: To assess whether incentives for practicing regular physical activities in fact help raising the frequency of exercising. Methods: Male and female subjects undergoing two to three assessments in the Check-Up Unit of Hospital Israelita Albert Einstein (HIAE) were evaluated by noting any increase in levels of physical activity, improvements in mean metabolic unit numbers, and the sensitization index. The International Physical Activity Questionnaire was applied to assess the sample. Results: There were 1,879 subjects − 1,559 (83%) males and 320 (17%) females – aged 20 to 76 years (mean age = 45.8 years, standard deviation ± 8.8) who underwent a Continued Health Review at the Center for Preventive Medicine of the HIAE, Check-Up Unit, Jardins. Initially, over half of the sample was insufficiently active (sedentary or poorly active); there were more women than men in this group. After the health review, most subjects increased their level of physical activity; this increase was higher among women. Males encouraged three times to exercising showed better results (increased level of physical activity) as compared to males encouraged twice for exercising. The best results in females were found in the group that went through two evaluations. This result is due to the fact that the sample of females comprising the group that received incentives on three occasions was small. This was also the only group that showed no increase in mean metabolic units. The sensitization index assessment in the overall sample was very satisfactory, as the expected results were achieved. Conclusions: These results show that motivational interventions are effective for raising the level of physical activity. We concluded that to encourage the practice of regular physical activity through information programs about its health benefits is very important.